IMPLEMENTATIF TENTANG PEMBUATAN KARTU KELUARGA DALAM KEPENDUDUKAN BERDASARKAN UNDANG -UNDANG NOMOR 24 TAHUN 2013 TENTANG ADMINISTRASI KEPENDUDUKAN DIKAITKAN DENGAN KOMUNITAS DAYAK HINDHU – BUDDHA BUMI SEGANDU INDRAMAYU - Imas Khaeriyah Primasari; Saeful Kholik (Problematika Hukum, 2017)
Population Administration geared to meet the rights of every person in the field of population administration without discrimination through a professional public service. Registration is done by recording biographical data resident population, recording on events reporting population and population census as well as the issuance of citizenship documents.46 Law No. 24 of 2013 concerning changes to law Number 23 of 2006 concerning Population Administration emphasizes that in orderly management of population administration must make a Deed of Liability, Identity Card, And of course the Family Card of course it regulates the orderly administration regardless of their race, culture and class that respect each other's faith as Dayak Budha Bumi Segandu Indramayu Regency who have been discriminatory towards the creation of family cards that still see tribes, customs and traditions of a particular group. The long-term goals and specific targets to be achieved from this study are to provide an understanding of the implications of sanctions if the family card is not accompanied by religion and knowledge of a group of Buddhist dayak tribes and the obstacles and efforts of the Indramayu Regency government in implementing Law Number 24 of 2013 concerning Amendments to Law Number 23 Year 2006 concerning Population Administration. The method that will be used in achieving these objectives is to use normative legal research methods (doctrinal research) which mainly analyze primary legal materials and secondary legal materials equipped with field data. The implementation of the model for the formation of a Family Card registration policy by the Dayak Bumi Budhha Segandhu tribe in Losarang Subdistrict, Puntang Village, Indramayu Regency, adheres to the difficulties of registering a family card or other administration, The findings in the field prove that the people of the Segandhu Buddhist Dayak tribe adherents also have offspring and implementing compulsory schooling for 9 years The implementation is not in line with the Law